If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x + 4 + -4x + -1(1 + -2x) = 3 x + 4 + -4x + (1 * -1 + -2x * -1) = 3 x + 4 + -4x + (-1 + 2x) = 3 Reorder the terms: 4 + -1 + x + -4x + 2x = 3 Combine like terms: 4 + -1 = 3 3 + x + -4x + 2x = 3 Combine like terms: x + -4x = -3x 3 + -3x + 2x = 3 Combine like terms: -3x + 2x = -1x 3 + -1x = 3 Add '-3' to each side of the equation. 3 + -3 + -1x = 3 + -3 Combine like terms: 3 + -3 = 0 0 + -1x = 3 + -3 -1x = 3 + -3 Combine like terms: 3 + -3 = 0 -1x = 0 Solving -1x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Divide each side by '-1'. x = 0 Simplifying x = 0
| 24/3=y | | -9d-8=4(d+2)-5d | | (3+y)/4=-y-8 | | r+11+8r=2 | | 10=-6t^2+13t+5 | | -12/12 | | r+11+8r=-2 | | 2n+8+(4)=10 | | 8=-10p+9p-7 | | P(p-3)=-2 | | P(p-3)4=-2 | | 10x=8(x-9) | | 5x+6=3x+5 | | 4x+7+2x+16=7x+2 | | 3r^3-15r^2+18r=0 | | 2x^4-9x^3+13x^2-x-5=0 | | 0=-6t^2+13t+5 | | 12x^2+15x^2=X | | x^2+bx+18=0 | | (5x-4)(7x-5)=0 | | .2(x-6)=2 | | 15k+k-21=105 | | 6q-178=2(6-4q)-5q | | -3w^2+4w=56 | | 4w^7+22w^6+10w^5= | | -3(x+5)=3(-1) | | 92=4/x | | x^1/3x^1/7 | | n+-4+-9= | | -18x-36+36-12x=-14 | | (x-17.7)+19.6=17.8 | | (4X-10)=(X) |